Pendampingan Penerapan Teknologi Fotografi dan Videografi di TBM Rumah Baca Bintang: Pengabdian - Malida Fatimah; Kristina Andriyani; Triana Noor Edwina Dewayani Soeharto (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity was carried out at TBM Rumah Baca Bintang, located in Argomulyo, Sedayu, Bantul, Yogyakarta. The program aimed to improve the facilitators’ ability to apply photography and videography technology in documenting and promoting literacy activities through digital media. The main problems faced by the partners included limited human resources in digital management, lack of technical skills, and minimal documentation and publication of literacy activities. The method combined training and mentoring, consisting of three stages: material delivery, technical practice, and mentoring on the results. The materials were presented through a training module that included topics on mobile photography equipment, pre-production and content planning, shooting techniques, and basic editing for social media publication. The pretest and post-test results showed an increase in participants’ understanding and skills, with all facilitators achieving a perfect score after the program. The participants were able to create and manage digital documentation independently using mobile devices. This activity successfully strengthened the digital literacy capacity of TBM Rumah Baca Bintang’s facilitators and encouraged the sustainability of literacy programs through creative and contextual digital media utilization.